Circulating Leukocytes and Antibody Isotype Reactivity in Rats Experimentally Infected with Different Burdens of Strongyloides venezuelensis, Before and After Treatment with Ivermectin or Dexamethasone - João Gustavo Mendes Rodrigues; Guilherme Silva Miranda; Genil Mororó Araújo Camelo; Caio Brandão Goes Gouveia; Deborah Aparecida Negrão-Corrêa (Tropical Medicine and Infectious Disease, 2026)
Strongyloidiasis is a neglected, potentially lifelong disease caused by Strongyloides stercoralis that can lead to a high mortality rate in immunocompromised hosts; therefore, it is necessary to increase the accuracy of infection diagnosis. In the current study, we used Wistar rats experimentally infected with different burdens of Strongyloides venezuelensis to characterize circulating leukocytes and IgM, IgG, IgG1, IgG2a, and IgA reactivity before and after anthelmintic treatment or immunosuppression. Infection, especially with 500 L3, induced an increase in circulating leukocytes, particularly during the acute phase. Animals treated with ivermectin showed complete elimination of the parasite and an early reduction in circulating eosinophils. The production of IgM, IgG, and IgG1 anti-L3 (infective larvae) and anti-Sv (adult worm) antigens was significantly elevated in all infected groups but did not allow differentiation between cured and infected animals. Treatment with dexamethasone delayed worm elimination and temporarily reduced cellular response and parasite-specific IgG production but did not alter IgM reactivity. IgG2a anti-L3 and anti-Sv reactivity showed a progressive reduction, returning to baseline levels in ivermectin-treated rats. IgA anti-ES/L3 (excretory and secretory larval antigens) reactivity significantly decreased in intestinal wash after parasitological cure. These data would help the development of more efficient immunodiagnostic alternatives for human strongyloidiasis based on antibody isotype reactivity.